Management of Integrated Development Programmes in Ibanda and Kiruhura districts in Western Uganda - Muzaare, Gerald (NIU Journal of Social Sciences; Vol 2 No 2 (2016): KIU Journal of Social Sciences, Vol. 2 No.2, September 2016, 2017)
This study examined the extent of management on integrated development programmes in the districts Ibanda and Kiruhura. The study aimed at establishing whether there is a significant difference in extent of management between the districts. Using a questionnaire method, data were collected from a sample of 93 local leaders and analyzed using means and t-test. The findings were that there was no significant difference between the districts. Therefore it was concluded that if programmes are to be well managed, districts deserve equal support from all the stakeholders in their efforts to better the lives of rural people, and rural development policy be strengthened. Keywords: Management, Plan, Leadership, Financial Management, Integrated Development.